Leveraging Geographic Research, Web Applications and Surveys in the Construction of Educational Strategies in Ecuador - Santos, Fabián (2024)
Communicating geographic research and contributing to the construction of regional educational strategies represent little-explored challenges. This paper takes a geographic research study that discusses territorial imbalances in access to higher education in Ecuador as an example. It describes a methodology based on developing a web application software (WAS) named “Brechas Educativas”. This software aims to disseminate research results and encourages users to reflect on their territories and the access to higher education for their student populations. Subsequently, we collected perceptions about the WAS, factors affecting academic performance and the assimilation of experiences post-COVID-19 pandemic through a survey. To achieve this, virtual workshops were conducted with 95 educational institutions (EIs) across Ecuador, complemented by email correspondence with a group of 3284 EIs. Our results enabled us to understand the good practices for developing WAS for scientific dissemination, the achievements and pitfalls in collecting opinions from the EIs and to draft focused strategies for educational decision-making in this area, informed by both app traffic and survey responses.